Cysts of the Snow Alga Chloromonas krienitzii (Chlorophyceae) Show Increased Tolerance to Ultraviolet Radiation and Elevated Visible Light - Procházková, Lenka; Remias, Daniel; Bilger, Wolfgang; Křížková, Heda; Řezanka, Tomáš; Nedbalová, Linda (Frontiers in Plant Science, 2020)
Melting mountainous snowfields are populated by extremophilic microorganisms. An alga causing orange snow above timberline in the High Tatra Mountains (Poland) was characterised using multiple methods examining its ultrastructure, genetics, life cycle, photosynthesis and ecophysiology. Based on light and electron microscopy and ITS2 rDNA, the species was identified as Chloromonas krienitzii (Chlorophyceae). Recently, the taxon was described from Japan. However, cellular adaptations to its harsh environment and details about the life cycle were so far unknown. In this study, the snow surface population consisted of egg-shaped cysts containing large numbers of lipid bodies filled presumably with the secondary carotenoid astaxanthin. The outer, spiked cell wall was shed during cell maturation. Before this developmental step, the cysts resembled a different snow alga, Chloromonas brevispina. The remaining, long-lasting smooth cell wall showed a striking UV-induced blue autofluorescence, indicating the presence of short wavelengths absorbing, protective compounds, potentially sporopollenin containing polyphenolic components. Applying a chlorophyll fluorescence assay on intact cells, a significant UV-A and UV-B screening capability of about 30 and 50%, respectively, was measured. Moreover, intracellular secondary carotenoids were responsible for a reduction of blue-green light absorbed by chloroplasts by about 50%. These results revealed the high capacity of cysts to reduce the impact of harmful UV and high visible irradiation to the chloroplast and nucleus when exposed at alpine snow surfaces during melting. Consistently, the observed photosynthetic performance of photosystem II (evaluated by fluorometry) showed no decline up to 2100 μmol photons m–2 s–1. Cysts accumulated high contents of polyunsaturated fatty acids (about 60% of total fatty acids), which are advantageous at low temperatures. In the course of this study, Chloromonas krienitzii was found also in Slovakia, Italy, Greece and the USA, indicating a widespread distribution in the Northern Hemisphere.